2014
DOI: 10.1080/10888691.2014.946030
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Differences in College Persistence: A Longitudinal Examination of Financial Circumstances, Family Obligations, and Discrimination in an Ethnically Diverse Sample

Abstract: Ethnic and generation differences in motivation and achievement have been well-established. However, less work has examined the role of social factors on educational outcomes among individuals from diverse backgrounds. With a longitudinal sample of 408 Latino, Asian, and European-American students, we examine family, discrimination, and financial factors in 12th grade and two years later as predictors of persistence four years after high school, and as mediators of ethnic and generation differences in persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…Specifically, Benner & Kim (2009a) found that contemporaneous experiences of discrimination were more likely to relate to depressive symptoms, whereas early discrimination experiences were more likely to relate to worse later academic outcomes, in Chinese American adolescents. Corroborating this finding, another study that sampled Asian and Latino children of immigrants found that high school discrimination experiences related to later academic outcomes, specifically college persistence (Witkow et al 2015).…”
Section: Transcultural and Culture-specific Stressorsmentioning
confidence: 95%
“…Specifically, Benner & Kim (2009a) found that contemporaneous experiences of discrimination were more likely to relate to depressive symptoms, whereas early discrimination experiences were more likely to relate to worse later academic outcomes, in Chinese American adolescents. Corroborating this finding, another study that sampled Asian and Latino children of immigrants found that high school discrimination experiences related to later academic outcomes, specifically college persistence (Witkow et al 2015).…”
Section: Transcultural and Culture-specific Stressorsmentioning
confidence: 95%
“…In fact, various SCCT studies have not examined academic achievement when exploring career development and vocational outcomes (Lubinski, 2010). With academic achievement being associated with college persistence among youth of color (Witkow, Huynh, & Fuligni, 2015), there is a need to explore variables, such as academic achievement, that influence career development of unique populations. As college degrees continue to be a necessary commodity for future generations, researchers are called to explore how academic performance is related to educational goals and its impact on career development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the more proximal variables is its function as a resilience factor for post-secondary students. Attending a college or university can be a very stressful transition, presenting an array of personal and interpersonal challenges for students (Pascarella and Terenzini, 2005), especially when having to move away from their home town (Witkow et al, 2015). This demographic, comprised mostly of young adults, leave the proximity of pre-existing relationships (like family and friends) and have to form new ones, as well as adapt to a more challenging academic load (Fussell et al, 2007).…”
Section: Trait Ei In Post-secondary Contextsmentioning
confidence: 99%